ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATWAKTUAN PELAPORAN KEUANGAN PADA PERUSAHAAN SUB SEKTOR PERTAMBANGAN LOGAM DAN MINERAL LAINNYA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2018 - Wiwit Hadi Parwoko; Dewi Saptantinah Puji Astuti; Sunarti Sunarti (Universitas Slamet Riyadi, 2020)
This study aims to find empirical evidence about the factors that affect thetimeliness of financial reporting of other metal and mineral mining sub-sectorslisted on the Indonesia Stock Exchange. The factors tested in this study areprofitability, company age, company size, leverage, liquidity, KAP reputation andownership structure. The sample in this study used 8 metal and mineral miningsub sector companies listed on the Indonesia Stock Exchange in the period 2013-2018 taken using purposive sampling. These factors are then tested by logisticregression at a significance level of 5 percent. The results of the study identifiedthat company age and KAP's reputation had a significant effect on the timelinessof financial reporting, while profitability, company size, leverage, liquidity andownership structure did not affect the timeliness of financial reporting in othermetal and mineral mining sub-sectors listed on the Indonesia Stock Exchange.